Misconceptions about the use of monsoons by dhows in East African waters - Datoo, B. A. (East African Geographical Review, 1970)
The East African coast has had maritime contacts with the peripheral lands of the Arabian Sea from time immemorial, and although dhows have been superseded by steamships since the latter part of the nineteenth century, a few still visit East Africa every year. Unless they are equipped with engines, movement of these sailing craft is dependent upon the monsoonal regime of the western Indian Ocean. However, popular ideas about monsoons constitute major misconceptions. These relate to the southern extent of the reliable northeast monsoon employed for the outward journey to East Africa, and the use of the southwest monsoon for the homeward passage to Arabia, Iran and India. This article seeks to correct these misconceptions on the basis of meteorological conditions in the western Indian Ocean, substantiated where possible by empirical evidence, contemporary and historical.
Keywords: Navigation – Zanzibar